A Shuffle-Based Statistical Approach for Robust Pseudogene Annotation - M. Barcelos, Pedro; Catanho, Marcos; B. de Miranda, Antônio; Haeusler, Edward H.; Lifschitz, Sérgio (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
The accurate annotation of pseudogenes is a significant challenge in genomics, as their decaying sequences often fall into a "twilight zone" of similarity that confounds automated methods. This paper describes a robust, homology-based methodology designed to overcome this issue. The core of the approach is a shuffle-based statistical evaluation used to establish a custom, empirically-derived significance threshold. This allows for the confident discrimination of true, biologically significant sequence remnants from stochastic background noise, providing a reliable framework for annotating pseudogenes and unannotated coding sequences in large-scale genomic projects.